Позывной "Матрос" - Агранович Владимир (Мысли о Родине, 2024)
Экземпляры: ЦБ/3/6 (20250512) / Инвентарный номер: 68033 / Цена: 624.00 / Сис.шифр: Р2 / Авт.знак: А 25 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6